2011
DOI: 10.1021/ie102573m
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Thermochemical Conversion of Glycerol to Simple and Polyhydric Alcohols Using Raney Nickel Catalyst

Abstract: The crude glycerol from biodiesel production possesses low economic values and alternative ways of converting it to valuable chemicals are needed to sustain the biodiesel industry. This study aimed to investigate the production of primary alcohols and propylene glycol from glycerol through a catalytic thermochemical process without an external supply of hydrogen. The effects of reaction time, water to glycerol ratio, and doses of catalyst on glycerol conversion and alcohol yields were investigated using a batc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 20 publications
1
34
0
7
Order By: Relevance
“…Results showed that glycerol conversion and ethanol selectivity are both improved as the reaction time was extended from 24 h to 48 h. Meanwhile, 1,2-PDO selectivity declined, which was assumed to be the result of further hydrogenolysis, as evidenced by the increase in ethanol and n-propanol selectivities. These results are in agreement with previous studies, in which 1,2-PDO is considered a precursor for ethanol and propanol production [17][18][19][20][21][22][23]44]. …”
Section: Effect Of Reaction Timesupporting
confidence: 93%
See 4 more Smart Citations
“…Results showed that glycerol conversion and ethanol selectivity are both improved as the reaction time was extended from 24 h to 48 h. Meanwhile, 1,2-PDO selectivity declined, which was assumed to be the result of further hydrogenolysis, as evidenced by the increase in ethanol and n-propanol selectivities. These results are in agreement with previous studies, in which 1,2-PDO is considered a precursor for ethanol and propanol production [17][18][19][20][21][22][23]44]. …”
Section: Effect Of Reaction Timesupporting
confidence: 93%
“…The conditions were chosen to get similar glycerol conversions and allow direct comparison on the catalyst performance. Similar glycerol conversions were achieved when 5 g of catalyst was reacted for 6 h, as compared to 10 g of the 25 wt % Ni/Ce-Mg (9:1 mol/mol) catalyst reacted for 24 h, which showed Raney ® Ni's superior activity in terms of rate of conversion [44]. However, it was observed that the catalyst developed in this study led to higher 1,2-PDO, ethanol, and overall selectivity towards desired hydrogenolysis products at all temperatures tested.…”
Section: Comparison With Raney ® Ni Catalystmentioning
confidence: 54%
See 3 more Smart Citations